1982
DOI: 10.4141/cjps82-121
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Method and Date of Pruning on Soil Organic Matter and Leaf Nutrient Concentrations of Lowbush Blueberries

Abstract: Lowbush blueberry (vac.iniunt angustifolium Ait.) plants were pruned mechanically by flail mowing, or thermally by oil burning in the spring or fall. The prunlng treatments had no effect on soil organic matter or pH. Leaf

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 3 publications
1
8
1
Order By: Relevance
“…Furthermore, there was no significant difference in the depth of the surface organic layer or the total carbon content of the surface 5 cm of soil between the unburned check and the average value across burning cycles, nor among burning cycles in 1986. Although these results support the findings of some (Hanson et al 1982), and contradict those of others (Trevett 1956;Smith and Hilton 1971;Trevett 1972), such factors as length of study, type of fuel and climatic conditions should be considered when making comparisons. A short-term (pruned once) study by Hanson et al (1982) in Maine determined that oil burning did not significantly For personal use only.…”
Section: Resultssupporting
confidence: 46%
See 2 more Smart Citations
“…Furthermore, there was no significant difference in the depth of the surface organic layer or the total carbon content of the surface 5 cm of soil between the unburned check and the average value across burning cycles, nor among burning cycles in 1986. Although these results support the findings of some (Hanson et al 1982), and contradict those of others (Trevett 1956;Smith and Hilton 1971;Trevett 1972), such factors as length of study, type of fuel and climatic conditions should be considered when making comparisons. A short-term (pruned once) study by Hanson et al (1982) in Maine determined that oil burning did not significantly For personal use only.…”
Section: Resultssupporting
confidence: 46%
“…This practice stimulates the growth of new stems from dormant buds on the rhizomes and increases yield (Hall 1955). While burn-pruning increases short-term yield, there is a concern that it reduces the surface organic layer where most of the rhizomes are located and that it would cause production to decline and blueberry fields to be destroyed (Trevett 1956;Black 1963;Kender et al 1964;Smith and Hilton 1971;Hanson et al 1982).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Leaf Ca concentration was lower than that reported by Bouchard and Gagnon (1987). Leaf Ca concentration may be diluted by greater foliar growth associated with fertilizer applications (Ismail et al 1981;Hanson et al 1982). In the Bouchard and Gagnon study (1987) pruning was done by burning, whereas in the current study, mechanical mowing was used.…”
Section: Resultsmentioning
confidence: 86%
“…Burning the plants leaves Ca-rich ash on the ground, increasing the amount of Ca available for uptake by new shoots (Smith and Hilton 1971). Ismail et al (1981) reported that pruning method had no influence on leaf nutrient concentrations whereas Hanson et al (1982) observed an increase of leaf N and P concentration and a decrease of leaf Ca concentration with burning compared with mowing method. Unlike Ca, leaf Mg concentration was comparable to that reported by Bouchard and Gagnon (1987) despite the different pruning techniques used as reported by Ismail et al (1981) and Hanson et al (1982).…”
Section: Resultsmentioning
confidence: 99%